APLIKASI PEMESANAN MAKANAN ONLINESHOP NYEMILICIOUSS BERBASIS ANDROID - Deni Erlansyah; Athiyyah Zahra (P3M Institut Teknologi Pagar Alam, 2023)
Nyemiliciouss is one of the Micro, Small and Medium Enterprises (MSMEs) in the city of Palembang, this business is a home-made ready-to-eat snack product. The main menu, Ichigo daifuku, is a typical Japanese mochi dish that is currently booming among the public. Ichigo daifuku is filled with red bean paste and strawberries. The fresh taste of strawberries combined with the mildly sweet red bean paste makes this sweet snack popular with many people. Interestingly, Nyemiliciouss presents 9 delicious mochi flavor variants. Currently, Nyemiliciouss is experiencing difficulties in serving orders and is still using records that are not yet computerized or still using a conventional system. The problem is that buyers have to wait too long to order food. Therefore, to overcome this problem the author created an application that can make it easier for customers to place orders using an Android cellphone to speed up the ordering process. This application aims to improve services for micro, small and medium enterprises (MSMEs), so that transactions can be carried out more quickly and accurately without customers having to come to the outlet. In this research, the Extreme Programming (XP) method is used to develop a food ordering application. This method involves a planning stage to analyze system requirements and user needs, as well as a design stage to determine the appearance and smoothness of the system to be developed.